Pelatihan Digital Marketing UMKM Kawasan Pondok Pesantren Rejoso Peterongan Jombang - Risnawati, Risnawati; Mas’adah, Mas’adah; Triono Singgih, Cuk; Galahartlambang, Yanuangga; Firdawati , Yulia (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The impact of COVID 19 has greatly reduced product marketing for the business world, including MSMEs, especially those still using traditional products. Based on these problems, MSME actors are required to make changes in marketing their products through social media or known as digital marketing. The purpose of this abdimas activity is to provide knowledge and training for MSMEs about digital marketing for marketing by utilizing social media. The method of abdimas activities are lectures, discussions and direct training to MSME actors. The abdimas participants, namely MSME actors in the Pondok Pesantren area, do not yet know the digital marketing system to offer products. The total number of associations is about 125 business actors who follow 25 people. The results from abdimas are that participants get additional knowledge and knowledge about digital marketing starting from the understanding, types, and uses for marketing MSME products and participants can create content and captions to support product picture/photo/video posts on Instagram accounts